2009
DOI: 10.1049/iet-rsn:20070176
|View full text |Cite
|
Sign up to set email alerts
|

Excitation matching procedure for sub-arrayed monopulse arrays with maximum directivity

Abstract: In this paper, the maximization of the directivity of compromise difference patterns in subarrayed monopulse linear array antennas with optimum sum mode is addressed by means of a two-stage excitation matching procedure. The knowledge of the independently optimum difference excitations, which provide the maximum directivity, is exploited with an efficient matching technique based on the contiguous partition method. Simple and reliable compromise solutions, characterized by a reduced complexity as well as easie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Similarly, Farina with different coauthors has given creative and pioneering contributions to the following aspects, including subarrayed weighting for SLC [25,26], subarrayed adaptation and superresolution [25][26][27], and subarray optimization [25,28]. Lombardo and his co-authors contributed great achievements to subarrayed adaptive processing and pattern control [29,30], SASP for thinned arrays [31,32], while Massa et al contributed in the fields of subarrayed weighting, synthesis of sum and difference patterns for monopulse [33][34][35][36]; Liao et al in the field of subarrayed 2 International Journal of Antennas and Propagation ABF, subarrayed STAP and subarray architectures [23,37,38]; Wang et al in the field of subarrayed STAP and subarray configuration [39][40][41][42]; Klemm in the field of the design of the subarray configuration for STAP [43], and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Farina with different coauthors has given creative and pioneering contributions to the following aspects, including subarrayed weighting for SLC [25,26], subarrayed adaptation and superresolution [25][26][27], and subarray optimization [25,28]. Lombardo and his co-authors contributed great achievements to subarrayed adaptive processing and pattern control [29,30], SASP for thinned arrays [31,32], while Massa et al contributed in the fields of subarrayed weighting, synthesis of sum and difference patterns for monopulse [33][34][35][36]; Liao et al in the field of subarrayed 2 International Journal of Antennas and Propagation ABF, subarrayed STAP and subarray architectures [23,37,38]; Wang et al in the field of subarrayed STAP and subarray configuration [39][40][41][42]; Klemm in the field of the design of the subarray configuration for STAP [43], and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Starting from a combinatorial formulation of the problem at hand, the authors use the Ant Colony Optimization (ACO) metaheuristics for determining the subarray configuration expressed as the optimal path inside a directed acyclic graph structure modeling the solution space. Some other recent and significant research efforts in this direction can be found in [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…An improvement to the excitation matching technique is introduced by Rocca et al [16] based on the ant colony algorithm for monopulse operation. Other subarray techniques based on hybrid and evolutionary optimisation solutions have been reported in literature [17][18][19][20][21][22][23][24][25][26][27].…”
Section: International Journal Of Antennas and Propagationmentioning
confidence: 99%